Answer:
y = 3
x =7
Explanation:
to solve this system of equations using substitution method we say, let
5x + 4y = -22 .................... equation 1
2x – 3y = 5...................... equation 2
from equation 2
2x - 3y = 5
2x = 5 + 3y
divide both sides by 2
we have;
2x/2 = (5+3y)/2
x =(5+3y)/2................................ equation 3
put x = (5+3y)/2 in equation 1
5x + 4y = -22 .................... equation 1
5(5+3y)/2 + 4y = -22
(25 + 15y)/2 + 4y = -22
multiply through by 2
25 + 15y + 8y = -44
25 + 23y = -44
collect the like terms
23y = -44 - 25
23y = -69
divide both sides by 23
23y/23 = -69/23
y = 3
put the value of y= 3 into equation 3
x =(5+3y)/2................................ equation 3
x = (5+3(3)]/2
x = 5+9/2
x =14/2
x =7